Perancangan dan Pembuatan Media Pembelajaran Android Menggunakan Smart Apps Creator 3 pada Mata Pelajaran Administrasi Infrastruktur Jaringan - Wijaya, Indra; Juwita, Astri Indah; Sardiyanti, Opi (SAFE-Network, 2025)
This study aims to determine the Valididy, prakticality adn effectivenees of the design and manufacture of Android learning media using Smart Apps Creator 3 in the subjeck of Network Infastructure Administration for Class XI TKJ 1 at SMK Negeri 2 Padang.. This study uses research development methods (Research & Development). The research subjects are 30 people. The research model used is the development research model (ADDIE Model), with the design steps of the development as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. the results of the validity test by the experts in the overall assessment validator is 87,00%, so that the level of validity can be interpreted Very Valid is Used. The results of the practicality test assesment total of 93,16%, so the level of practicality can be interpreted Very Practical to used. The results of the overall effectiveness the overall effectiveness test assesment are 87,87%, so that the level of effectiveness can be interpreted as Very Effectively used. In conclusion, based on the assessment and expert input as well as the results of the field trial of the Android Learning Media Application as a Learning medium, it has been tested for feasibility, excellence, and can be used in the learning process in the Class XI TKJ 1 Network infrastructure Administration subject at SMK Negeri 2 Padang.